Kedwibahasaan Dalam Novel Kenanga Karya Oka Rusmini - Simatupang, Jernita; Siahaan, Putri Damayanti; Simorangkir, Shely; Sari, Yuliana (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the role and influence of bilingualism in the novel Kenanga by Oka Rusmina. This study uses a qualitative research method using sociolinguistic studies. Based on this study, it is concluded that bilingualism in the novel Kenanga by Oka Rusmini observes the use of two languages, Indonesian and Balinese, as an important part of the identities of the characters and the cultural life depicted in the novel. Bilingualism in this novel not only reflects language differences, but also describes cultural differences, values, and social dynamics in Balinese society. The use of Balinese illustrates closeness to local traditions and identities, while Indonesian shows openness to modernization and broader intercultural relations. Through this bilingualism, the Novel Kenanga by Oka Rusmini shows the complexity of individual identity rooted in tradition. However, it also tries to adapt to social change. This novel shows the importance of language as a means of understanding identity and intercultural relations.